Effects of oxaliplatin and oleic acid Gc‐protein‐derived macrophage‐activating factor on murine and human microglia. Issue 9 (18th March 2015) - Branca, Jacopo J.V.; Morucci, Gabriele; Malentacchi, Francesca; Gelmini, Stefania; Ruggiero, Marco; Pacini, Stefania
Abstract : The biological properties and characteristics of microglia in rodents have been widely described, but little is known about these features in human microglia. Several murine microglial cell lines are used to investigate neurodegenerative and neuroinflammatory conditions; however, the extrapolation of the results to human conditions is frequently met with criticism because of the possibility of species‐specific differences. This study compares the effects of oxaliplatin and of oleic acid Gc‐protein‐derived macrophage‐activating factor (OA‐GcMAF) on two microglial cell lines, murine BV‐2 cells and human C13NJ cells. Cell viability, cAMP levels, microglial activation, and vascular endothelial growth factor (VEGF) expression were evaluated. Our data demonstrate that oxaliplatin induced a significant decrease in cell viability in BV‐2 and in C13NJ cells and that this effect was not reversed with OA‐GcMAF treatment. The signal transduction pathway involving cAMP/VEGF was activated after treatment with oxaliplatin and/or OA‐GcMAF in both cell lines. OA‐GcMAF induced a significant increase in microglia activation, as evidenced by the expression of the B7‐2 protein, in BV‐2 as well as in C13NJ cells that was not associated with a concomitant increase in cell number. Furthermore, the effects of oxaliplatin and OA‐GcMAF on coculture morphology and apoptosis were evaluated. Oxaliplatin‐induced cell damage and apoptosis were nearly completely reversed by OA‐GcMAF treatment in both BV‐2/SH‐SY5Y and C13NJ/SH‐SY5Y cocultures. Our data show that murine and human microglia share common signal transduction pathways and activation mechanisms, suggesting that the murine BV‐2 cell line may represent an excellent model for studying human microglia. © 2015 Wiley Periodicals, Inc.